2022
DOI: 10.12973/eu-jer.11.4.2487
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Nature of Science in Physics Textbooks of Cycle 4 Fundamental Schools in Burundi

Abstract: <p style="text-align: justify;">Guided by the analytical framework in the current literature, whereby ten nature of science (NOS) aspects were targeted, this study aims at assessing the extent to which the three physics textbooks for Cycle 4 of Fundamental Schools in Burundi represent the NOS aspects. The quantitative embedded research design which combines the qualitative and quantitative to both the representations of text and images were applied to collect and analyses data. Three physics textbooks us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The deficit of NOS representation in science curricula and limited interventions on NOS aspects in teaching aids materials are worrisome in East African community countries (Kinyota, 2020;Kinyota & Rwimo, 2022;Munezero et al, 2022). For instance, in a study by Bugingo et al (2022a), a very poor, vague representation of NOS was identified from four senior secondary school physics curricula from Rwanda, Burundi, Uganda and Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…The deficit of NOS representation in science curricula and limited interventions on NOS aspects in teaching aids materials are worrisome in East African community countries (Kinyota, 2020;Kinyota & Rwimo, 2022;Munezero et al, 2022). For instance, in a study by Bugingo et al (2022a), a very poor, vague representation of NOS was identified from four senior secondary school physics curricula from Rwanda, Burundi, Uganda and Tanzania.…”
Section: Introductionmentioning
confidence: 99%